“Desarrollo del lenguaje verbal en sub inicial 2 en la Unidad Educativa Juan Abel Echeverría” - Muso Muso, Doris Zenaida (2023)
Language development is a complex process that occurs in interaction with different areas of development. This research was based on the problem: Insufficiency in the development of verbal language in the children of sub-level II, and its objective was to diagnose the development of verbal language in sub-level II of the "Unidad Educativa Juan Abel Echeverría." Where a qualitative approach, bibliographic, exploratory and descriptive research was carried out in which techniques such as the interview and the observation sheet were applied with their respective instruments such as the guide of questions and checklists, the interview was carried out with one tutor teacher and the checklist with 23 children of the educational unit, the results of which allowed the following conclusions to be reached. From the teachers' point of view, it is evident that there is a lack of knowledge of the strategies to stimulate verbal language, sometimes they may have difficulties in identifying children with pronunciation problems or language delays in time. It is important to note that many of these shortcomings can be addressed with appropriate training and solid institutional support. From observation of the children, it is evident that pronunciation and stuttering are common challenges in children's speech and language development, these problems can vary in severity and presentation, but their impact on a child's communication and self-esteem can be significant. Finally, in conclusion, verbal language development needs to be stimulated from an early age for its integral development, from a cognitive, psychomotor, and affective point of view, taking into account that it is fundamental to address these problems early and effectively through identification, stimulation, and intervention with appropriate support.